1981
DOI: 10.1126/science.211.4485.887
|View full text |Cite
|
Sign up to set email alerts
|

Specialization: Species Property or Local Phenomenon?

Abstract: Many herbivorous insects have generalized diets over the species' entire geographical ranges but they function as specialists with restricted diets in local communities. Local feeding specialization can be produced by biochemical, behavioral, ecological, and evolutionary processes. Much evidence is incompatible with the widely held assumptions that diet breadth is a species characteristic and that specialization among herbivorous insects implies greater efficiency and less niche overlap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
554
1
2

Year Published

1986
1986
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 781 publications
(578 citation statements)
references
References 117 publications
17
554
1
2
Order By: Relevance
“…The differential ability of plants to attract natural enemies may even be responsible for further dietary specialization of herbivores exploiting specific plant taxa like the Cruciferae (Yano, 1994). For example, opposing choices at the plant-level could benefit the herbivore and lead to enemy-free space shaping host-parasitoid interactions (Fox and Morrow, 1981;Fox and Eisenbach, 1992;Bigger and Fox, 1997;Gratton and Welter, 1999;Oppenheim and Gould, 2002). If host-parasitoid interactions in ecosystems are to be understood, foraging behavior of parasitoids must be studied in relation to inter-and intraspecific variation in plant-derived infochemicals.…”
Section: Introductionmentioning
confidence: 99%
“…The differential ability of plants to attract natural enemies may even be responsible for further dietary specialization of herbivores exploiting specific plant taxa like the Cruciferae (Yano, 1994). For example, opposing choices at the plant-level could benefit the herbivore and lead to enemy-free space shaping host-parasitoid interactions (Fox and Morrow, 1981;Fox and Eisenbach, 1992;Bigger and Fox, 1997;Gratton and Welter, 1999;Oppenheim and Gould, 2002). If host-parasitoid interactions in ecosystems are to be understood, foraging behavior of parasitoids must be studied in relation to inter-and intraspecific variation in plant-derived infochemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Although host specificity can vary to some degree among different populations of the same parasite species across its geographical range, it still represents a true character of a parasite species, being less variable within parasite species than among parasite species (Krasnov et al 2004 a). This suggests that the level of host specificity is subjected to natural selection rather than merely reflecting the local restrictions caused by a variety of ecological, morphological, chemical and/ or genetic factors (Fox and Morrow, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…From an evolutionary perspective, selection for higher or lower levels of host specificity (or, in a broader sense, ecological specialization) is affected by a variety of both parasite (=forager)-related and host (=resource)-related factors (Fox and Morrow, 1981 ;Futuyama and Moreno, 1988 ;Fry, 1996 ;Desdevises et al 2002). In particular, the models of Ward (1992) suggested that species tend to specialize on predictable resources, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…They may also be cryptic, as host adaptation may be behaviorally or physiologically rather than morphologically based. Not for nothing were herbivorous insects focal subjects for early discussions of sibling species [7,8] and later evaluations of intraspecific ecological heterogeneity [23]. These many International Journal of Ecology 3 sources of variation led to terminological confusion and a need for clear distinctions [10].…”
Section: The Kinds Of Biological Variationmentioning
confidence: 99%